THE INFLUENCE OF TAX AGGRESIVENESS ON FIRM VALUE WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Cristin Puspitaningrum; Mulyadi Noto Soetardjo (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The objective of this study is to investigate whether tax aggresiveness has an impact on firm value. In addition, this study also examines whether the mechanism of corporate governance influences the relationship between tax aggresiveness and firm value. Examining the moderating effect of corporate governance in the relationship between tax aggresiveness and firm value for the context of Indonesia is still rarely done. Using 213 firm-year samples from 2015-2019 data of 76 public firms registered at BEI from consumer cyclinal sector, this study regresses (1) tax aggresiveness toward firm value, (2) the interaction between tax aggresiveness and corporate governance toward firm value. The test result provides an evidence that tax aggresiveness has a negative impact on firm value. However, this study does not provide an empirical evidence that the influence of tax aggresiveness on firm value can be moderated by corporate governance mechanism.